2005
DOI: 10.4197/med.12-1.1
|View full text |Cite
|
Sign up to set email alerts
|

An Ideal Selective Anti-Cancer Agent In Vitro: I-Tissue Culture Study of Human Lung Cancer Cells A549

Abstract: Management of cancer is one of the challenging problems in medical practice as there are no available medical modalities that can selectively kill cancer cells without adverse effect on normal living cells or the functions of vital organs. Tissue culture of human lung cancer cells (A549) was used in studying the effect of agent, PM 701, to test its effect on the behavior of the cancer cells as compared with that of normal cells (human skin fibroblasts). This new agent proved to be effective in killing lung can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…The results of the current study of the cytotoxic effects of purified fractions of PMF on different types of cancer cell lines are in accord with those of previous studies [43][44][45][46][47] reporting the cytotoxic effect of PM701 (lyophilized camel urine) on cancer cell lines such as A549, L1210, HCT116, HepG2, MCF-7 and U251. Moreover, other fractions of camel urine such as PM701 and its bioactive fraction PMF and sub-fraction PMFK were shown to have cytotoxic properties against different cancer cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the current study of the cytotoxic effects of purified fractions of PMF on different types of cancer cell lines are in accord with those of previous studies [43][44][45][46][47] reporting the cytotoxic effect of PM701 (lyophilized camel urine) on cancer cell lines such as A549, L1210, HCT116, HepG2, MCF-7 and U251. Moreover, other fractions of camel urine such as PM701 and its bioactive fraction PMF and sub-fraction PMFK were shown to have cytotoxic properties against different cancer cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…As with the current study, a previous study [41][42][43][44][45][46] demonstrated that PM701, its bioactive fraction (PMF), and its sub-fraction (PMFK) all exhibit anti-cancer activity. Another study examined the effect of lyophilized PM701 and its bioactive fractions on the growth of breast cancer cells (MCF-7).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Both camel milk and urine are among natural products endowed in agents with such desirable characteristics. These products possess supreme cytotoxic effect against various cancer cells and cell lines (Table 1) [9][10][11]16,23,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Cytotoxic Effectmentioning
confidence: 99%
“…Lactoferrin is found to bind with insulin-like growth factor-binding protein-3 [97], thereby act by altering the availability or stability of insulin-like growth factor, a known regulator of the phosphatidylinositol 3-kinase/Akt pathway [98]. Accordingly, camel urine possess supreme anti-proliferative effect on many lines of cancer cell possibly through the induction of the cyclin dependent kinase inhibitor p21 as it is found to up-regulates p21 in the p53-defective cancer cells [39,99]. Anti-proliferative effect of camel urine is significantly influenced by breeds, age, sex and other camel characteristics.…”
Section: Apoptotic Effectmentioning
confidence: 99%